2020
DOI: 10.1101/2020.01.28.923755
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diverse cell stimulation kinetics identify predictive signal transduction models

Abstract: The drive to understand cell signaling responses to environmental, chemical and genetic perturbations has produced outstanding fits of computational models to increasingly intricate experiments, yet predicting quantitative responses for new biological conditions remains challenging. Overcoming this challenge depends not only on good models and detailed experimental data but perhaps more so on how well the two are integrated. Our quantitative, live single-cell fluorescence imaging datasets and computational fra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…The high osmolarity glycerol (HOG) MAPK pathway in the budding yeast Saccharomyces cerevisiae (Figure 3A) is an ideal model system (Brewster et al, 1993;Saito and Posas, 2012;Brewster and Gustin, 2014) for addressing the question how do rate sensitivity and rate thresholds impact cell signaling and phenotype (Thiemicke et al, 2019;Jashnsaz et al, 2020;Johnson et al, 2021). At the molecular level, pioneering studies found that one signaling branch is activated through the Synthetic Lethal of N-end rule (Sln1) osmosensing histidine protein kinase leading to activation of the MAPKKK's Suppressor of Sensor Kinase (Ssk2) and its paralog Ssk22 and converging on the MAPKK Polymyxin B Sensitivity (Pbs2) kinase through several intermediate proteins.…”
Section: Concentration and Rate Thresholds Regulate Yeast Stress Resp...mentioning
confidence: 99%
See 2 more Smart Citations
“…The high osmolarity glycerol (HOG) MAPK pathway in the budding yeast Saccharomyces cerevisiae (Figure 3A) is an ideal model system (Brewster et al, 1993;Saito and Posas, 2012;Brewster and Gustin, 2014) for addressing the question how do rate sensitivity and rate thresholds impact cell signaling and phenotype (Thiemicke et al, 2019;Jashnsaz et al, 2020;Johnson et al, 2021). At the molecular level, pioneering studies found that one signaling branch is activated through the Synthetic Lethal of N-end rule (Sln1) osmosensing histidine protein kinase leading to activation of the MAPKKK's Suppressor of Sensor Kinase (Ssk2) and its paralog Ssk22 and converging on the MAPKK Polymyxin B Sensitivity (Pbs2) kinase through several intermediate proteins.…”
Section: Concentration and Rate Thresholds Regulate Yeast Stress Resp...mentioning
confidence: 99%
“…Activated Hog1 controls the regulation of cellular osmoadaptation and survival (Saito and Posas, 2012;Mitchell et al, 2015;Johnson et al, 2021). Because of this behavior of Hog1 nuclear enrichment, single-cell time-lapse microscopy and analysis have proven an excellent and sensitive way to monitor signaling responses to dynamic stimulation patterns in real-time (Figure 3) (Hersen et al, 2008;Mettetal et al, 2008;Muzzey et al, 2009;Patterson et al, 2010;Munsky et al, 2012;Mitchell et al, 2015;Granados et al, 2017;Thiemicke et al, 2019;Jashnsaz et al, 2021;Johnson et al, 2021). This single-cell analysis of Hog1 nuclear localization response to instant osmotic stress resulted in the discovery of perfect adaptation in this pathway (Figures 3C-E) (Hersen et al, 2008;Mettetal et al, 2008;Muzzey et al, 2009).…”
Section: Concentration and Rate Thresholds Regulate Yeast Stress Resp...mentioning
confidence: 99%
See 1 more Smart Citation